DETERMINATION OF SUBSURFACE TEMPERATURE DISTRIBUTION USING DIGITAL SENSOR DS18S20 (Case study in Cangar Hot Spring Area, Batu Region) - Fatoni, Amrin; Sunaryo, Sunaryo; Dharmawan, Hari Arief (Physics Student Journal, 2014)
The research of a subsurface temperature distribution has been performed in Cangar hot spring area, BatuÂ  city, East Java. The research was conducted using a DS18S20 sensor that was equipped with a CAN bus and provided more flexibility and practicability in temperature measurement for multiple measurement points that are far apart (~100m). The temperature measurement was carried out in 4 points at depth of 1.5 m each point with coverage area of 3x6 m2. From measurement result, temperature distribution was achieved at every different depth from 3 sensors with a space of 0.5m, The result of this study shows that the temperature around Cangar hot spring area is about 22oC - 33âC with a thermal gradient values ââranging from 0.32oC/m to 0.8Â°C/m. Correlation with the geological of study area, shows that the temperature anomaly was influenced by the heat flow of the heat source from volcanic magma chamber of Arjuno-Welirang volcano around the Cangar hot spring area. Keywords: Subsurface temperature, temperature distribution, DS1820 sensor, Cangar.